Future Application of Oncolytic Viruses for Cancer Treatment - Lesmana, Jevon Aaron; Jo, Juandy (Medicinus, 2023)
Cancer treatments have developed over the years. A particular improvement is the utilization of oncolytic viruses to treat cancers. Oncolytic viruses are one of the immunotherapeutic tools that potentially could provide good results and benefits to the patients. Oncolytic viruses could mediate antitumor effects. Indeed, the connection between viral infections and cancer treatment have been reported historically. It is known that oncolytic viruses prefer to infect cancer cells rather than normal cells, resulting in the presentation of tumor-associated antigens to the immune system, boosting immunological activity in the tumor microenvironment, as well as assisting in the expression of inflammatory and immunomodulatory cytokines. Oncolytic viruses are a novel regimen in the cancer therapy, in which knowledge and technology of utilizing oncolytic viruses to treat cancer are still evolving. Importantly, clinical trials demonstrated that the viruses were well tolerated by cancer patients. Considering its potency and prospect, oncolytic viral treatments could be a useful additional tool for cancer therapy.